Electrodes Based on Zeolites Modified with Cobalt And/Or Molybdenum for Pesticide Degradation: Part Ii—2,4,6-Trichlorophenol Degradation - Ureta-Zanartu, M; Aspee-Lamas, A; Berrios-Guinez, C; Fernandez-Vidal, F; Barrías-González, P; Castro-Laroze, J (Springer Science and Business Media Deutschland GmbH, 2021)
2,4,6-trichlorophenol (TCP) is a persistent pollutant introduced in water by industrial processes and pesticides. We have studied the electrooxidation of TCP on glassy carbon (GC) electrodes drop-coated with a suspension containing Mo- and/or Co-modified zeolite, graphite, and Nafion® perfluorinated ion-exchange resin in distilled water. Three zeolites, Linde type A (ZA), Faujasite (ZY) and MFI (ZSM-5), of different hydrophilic/hydrophobic character, were modified with molybdenum and/or cobalt by the wet impregnation method and characterized by Fourier-transform infrared spectroscopy with attenuated total reflection and temperature programmed reduction. The electrochemical study included cyclic voltammetry, electrochemical impedance spectroscopy, and electrolysis at controlled potential. High performance liquid chromatography and mass spectrometry allowed detecting the following reaction products: 2,6-dichloro-1,4-benzoquinone, 2,6-dichloro-1,4-hydroquinone, 3,5-dichloro-2-hydroxy-1,4-benzoquinone, and malic, maleic, picric, and acetic acids. A maximum degradation of about 90% was reached after 4 h of electrolysis at 0.83 V vs Ag/AgCl/KCl 3 M, using a GC/graphite-ZSM5Mo electrode. The electrodes modified with Mo, and especially that with ZSM5, the most hydrophobic zeolite, were active for the degradation of TCP. We conclude that the main role of the Mo species is to catalyze the hydrogen peroxide decomposition yielding reactive singlet oxygen, as evidenced by the pink color of 3,5-dichloro-2-hydroxy-1,4-benzoquinoneand confirmed by mass spectrometry. [Figure not available: see fulltext.] © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.